Nationality Versus Global Citizenship Towards the Realization of Sustainable Development Goals: Ahmadou Kouroumaâ€™s Perspective - Mawuloe Koffi, Kodah; Ofosu, Addo-Danquah (European Scientific Journal, ESJ, 2018)
In the face of the fast depletion of natural resources worldwide resulting from industrial and economic cannibalism, selfishness and marginalization are becoming more and more pronounced in a globalizing world. The phenomena of selfishness and marginalization are manifest in the introduction of stringent immigration laws by most industrialized countries in the North to ward off migrants from the less developed economies in the South; and also the reinforcement of existing laws by the latter to protect their citizens and natural resources in recent years. Issues of national identity, territorial integrity as against the centrality of humanity remain an Achilles heel toward the attainment of the Sustainable Development Goals (SDGs). As far as 1968, Ahmadou Kourouma, an Ivorian novelist, in his very first narrative text, â€œLes Soleils des IndÃ©pendancesâ€ later translated into English as The Suns of Independence, raised the tragic dilemma of national identity at the expense of â€˜human identityâ€™. In the absence of concrete steps to address the issues over the years, Liberia, Sierra Leone and La CÃ´te dâ€™Ivoire were engulfed in intestine civil strife over two decades later. The main causes of this strife are found in the irrational quest for self-identity in the name of nationality and ethnic superiority for greater access and control of â€œnationalâ€ resources. This paper examines the upsurge of socioeconomic and political exclusion, and the potential threats they pose to the realization of the recently launched Sustainable Development Goals. It is done through a critical reading of Kouroumaâ€™s The Suns of Independence, Allah is not obliged and â€˜Quand on refuse, on dit nonâ€™. The study is posited within the analytical framework of literary studies and sociocriticism